Association Between Low Blood Pressure and Clinical Outcomes in Patients With Acute Ischemic Stroke. Issue 1 (January 2020) - Verschoof, Merelijne A.; Groot, Adrien E.; Vermeij, Jan-Dirk; Westendorp, Willeke F.; van den Berg, Sophie A.; Nederkoorn, Paul J.; van de Beek, Diederik; Coutinho, Jonathan M.
Abstract : Background and Purpose—: Low blood pressure is uncommon in patients with acute ischemic stroke (AIS). We assessed the association between baseline low blood pressure and outcomes in patients with AIS. Methods—: Post hoc analysis of the PASS (Preventive Antibiotics in Stroke Study). We compared patients with AIS and low (<10th percentile) baseline systolic blood pressure (SBP) to patients with normal SBP (≥10th percentile <185 mm Hg). The first SBP measured at the Emergency Department was used. Outcomes included in-hospital mortality, major complications <7 days of stroke onset, and functional outcome at 90 days (modified Rankin scale score). We used regression analysis to calculate (common) odds ratios and adjusted for predefined prognostic factors. Results—: Two thousand one hundred twenty-four out of 2538 patients had AIS. The cutoff for low SBP was 130 mm Hg (n=212; range, 70–129 mm Hg). One thousand four hundred forty patients had a normal SBP (range, 130–184 mm Hg). Low SBP was associated with an increased risk of in-hospital mortality (8.0% versus 4.2%; adjusted odds ratio [aOR], 1.58; 95% CI, 1.13–2.21) and complications (16.0% versus 6.5%; aOR, 2.56; 95% CI, 1.60–4.10). Specifically, heart failure (2.4% versus 0.1%; aOR, 17.85; 95% CI, 3.36–94.86), gastrointestinal bleeding (1.9% versus 0.1%; aOR, 26.04; 95% CI, 2.83–239.30), and sepsis (3.3% versus 0.5%; aOR, 5.53; 95% CI, 1.84–16.67) were more common in patients with low SBP. Functional outcome at 90 days did not differ (shift towards worse outcome: adjusted common odds ratio, 1.24; 95% CI, 0.95–1.61). Conclusions—: Whether it is cause or consequence, low SBP at presentation in patients with AIS was associated with an increased risk of in-hospital mortality and complications, specifically heart failure, gastrointestinal bleeding, and sepsis. Clinicians should be vigilant for potentially treatable complications. Clinical Trial Registration—: URL: https://www.controlled-trials.com . Unique identifier: ISRCTN66140176. Abstract : Supplemental Digital Content is available in the text.